THE EFFECT OF MAYBELLINE SOCIAL MEDIA MARKETING (FACEBOOK, YOUTUBE, INSTAGRAM) ON CONSUMER PURCHASE DECISION (CASE STUDY: SAM RATULANGI UNIVERSITY STUDENTS) - Caecilia, Pijoh Meliani; Kindangen, Paulus .; Tumewu, Ferdinand . (FEB Universitas Sam Ratulangi Manado, 2017)
Abstract: Social media is trending. With the number of users rising each day, it becomes a better platform for business to communicate with their consumers. Social media provide business promotes their products or services. In social media consumers are actively talking about their experience and opinions about the products they have tried or even heard about it. This activity may affect the consumer to purchasing. This research aims to explain how the influence of Maybelline social media marketing (Facebook, YouTube, Instagram) on consumer purchase decision. Quantitative research method used for the purpose of this research. The sample size of this research is 100 Sam Ratulangi University students who are Maybelline consumers and already see Maybelline social media marketing. Purposive sampling was used by collecting data through online questionnaire. The research finds that Maybelline social media marketing affect on five stages of purchasing decision process. Maybelline marketing on YouTube and Instagram have positive effect on purchase decision. Otherwise, Maybelline marketing on Facebook has negative effect on purchase decision. Therefore, Maybelline needs to keep up their social media marketing. Keywords: social media marketing, maybelline, consumer purchase decision.